Smoking Cessation at the Community Pharmacy: Determinants of Success from a Real-Life Practice - Mónica Condinho; Isabel Ramalhinho; Carlos Sinogas (Pharmacy, 2021)
The objectives of this study are to report the contribution of pharmacists to smoking cessation and study the determinants of smoking cessation success in eight pharmacies in Portugal (south) between 2009 and 2019. A real-life study was conducted with a sample of smokers who participated in pharmacist consultations. The sample included 135 smokers (average age of 47.9 ± 1.21 years), 79 (58.5%) of whom were male. In parallel with the motivation and behavioral approach, 116 (85.9%) smokers received pharmacological therapies: 108 (80.0%) were treated with nicotine replacement products and eight (5.9%) with non-nicotine medications. The interventions resulted in 70 (51.9%) smokers complying with the quit day, of whom 59 (43.7%) were smoking-abstinent at the end of the first month. Success rates were reduced to 32.6%, 28.1%, and 20.7% at the end of the 3rd, 6th, and 12th months, respectively. Smoking cessation was more successful for the participants receiving pharmacological therapies (Fisher’s exact test, p < 0.001) and those who participated in more pharmacist consultations (χ2 = 59.994, p < 0.001) and more telephone sessions (χ2 = 17.845, p < 0.001). Pharmacists can contribute significantly to the promotion of smoking cessation. Smokers who are more thoroughly followed up by pharmacists showed increased success rates when compared with smokers having fewer sessions with pharmacists.